A novel yeast-derived aldehyde-reducing compound MF001 protects against alcohol-induced liver damage. - Eun-Ho Lee; Min-Hee Seo; Soo-Young Park; Sulagna Mukherjee; Jae-Ho Lee; Sora Kang; Ji-Yu Lee; Namgyu Lee; Hung Taeck Kwon; Seung-Soon Im (PLoS ONE)
Alcohol-induced fatty liver disease is a significant contributor to global mortality, primarily resulting from excessive alcohol consumption and subsequent hepatic damage. This study investigated the therapeutic potential of MF001, an aldehyde-reducing compound derived from the yeast Saccharomyces cerevisiae in alcohol-induced liver damage. Using a Lieber-DeCarli ethanol diet-induced live disease model, we assessed the effects of MF001 on lipogenesis, oxidative stress, and inflammation. MF001 treatment significantly reduced lipid accumulation, as indicated by decreased expression of lipogenic genes. Moreover, MF001 suppresses reactive oxygen species (ROS) production indicated by reduced malondialdehyde levels and ROS-associated inflammatory markers, including Tnf-α, Il-6, and Mcp-1. Histological analysis revealed decreased hepatic lipid deposition and inflammation following MF001 administration. Furthermore, MF001 modulated alcohol metabolism by downregulating Cyp2e1 and Adh1, thereby decreasing acetaldehyde accumulation and improving liver function, as evidenced by normalized ALT and AST levels. Our findings suggest that MF001 alleviates alcohol-induced liver damage through its anti-inflammatory, antioxidant, and lipid-lowering properties, highlighting its potential as a function agent for preventing and treating alcohol-induced fatty liver disease.